Dutch Protestant Missionaries in Formosa in the 17th Century - Puspitasari, Ni Wayan Radita Novi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2023)
The history of Dutch Protestant missionaries Formosa in the seventeenth century made a great contribution to the Christian spread in Asia. The beginning of the 1620s was the starting point of the establishment of the churches in Formosa. This study focuses on the Christian conversion in Formosa, which is based on the Dutch published archives and current research. The research aims to describe the process of Christian propagation in this area. Methodologically, the book “The Formosan Encounter. Notes on Formosa’s Aboriginal Society: A Selection of Documents from Dutch Archival Sources, I: 1623-1635; II: 1636-1645; and III: 1646-1654 that published in two languages, Dutch, and English” will be used as the main source in which qualitative approach is used to collect the primary and secondary data for analyzing this article. As a result, this research comes to the following conclusions, such as the missionaries used the educational method as a foundation for propagation and the result of giving the education was opposed by the Formosan’s old religion.